THE EFFECT OF ZIG-ZAG RUNNING EXERCISES ON THE DRIVING ABILITY IN FOOTBALL GAMES OF EXTRACURRICULAR PARTICIPANTS IN STATE PRIMARY SCHOOLS 10209989 NEW FIELD: PENGARUH LATIHAN LARI ZIG-ZAG TERHADAP KEMAMPUAN MENGGIRING DALAM PERMAINAN SEPAK BOLA PESERTA EKSTRAKURIKULER DI SD NEGERI 10209989 MEDAN BARU - Iin Farlina (LPPM UPMI, 2023)
This study aims to determine the effect of Zig-Zag running training on the dribbling ability of extracurricular participants in the soccer game at SD Negeri 10209989 Medan Baru. This type of research is experimental research. This research aims to prove the effect of training using the zig-zag training method on increasing dribbling agility. According to Burhan Nurgiyantoro, et al (2004:20-21) population is all members of research subjects who have similar characteristics. The population used in this research were 30 SD NEGERI 10209989 soccer players. The research instrument used for data collection in this study was a test. The tool used to measure ball dribbling skills is a stopwatch. The data collection technique in this research used a test of medribbling the ball through the stake. The data that will be collected in this research is pre-test data on dribbling the ball through stakes before the sample is given treatment, and post-test data after the sample is given treatment using the zig-zag training method. Before testing the hypothesis, it is necessary to test the prerequisites. Testing of measurement data related to research results aims to help make the analysis better. For this reason, in this research the normality and homogeneity of the data will be calculated. The results of the t-test show that >count>ttable (14.102>2.093) and the probability significance value is 0.000<0.05, meaning that there is an influence of zig-zag running training on the dribbling ability in football games of extracurricular participants at SD NEGERI 10209989 Medan Baru. Before being given zig-zag running training on dribbling skills in football games, extracurricular participants at SD NEGERI 10209989 Medan Baru had a pretest average of 18.19 seconds and at the posttest it increased to 16.49 seconds. It turns out that the average size after being given zig-zag running training increased by 2.61 or 13.01%.